PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK AEROSTREET: STUDI PADA KONSUMEN AEROSTREET KEDOYA UTARA - Papilaya, Yeremia; Kramadibrata, Budi Santosa (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
The rapid development of technology where almost everything is digital has a huge impact in the business world. One example is in the fashion industry, starting from technology that supports the process of making a fashion product, forming a product brand image, to marketing its products because of the flow of information and communication that can reach very widely in an easy and fast way without being limited by space and time through the internet, be it social media, e-commerce, etc. The author is interested in conducting research on the influence of promotion and product quality on purchasing decisions for Aerostreet products in North Kedoya. This study used quantitative research methods with a sample of 347 respondents. The results of this study show respondents strongly agree that promotion and product quality get a good value, evidenced by the positive influence on promotion and product quality on purchasing decisions in the results of this study. The conclusion of this study is that partial and simultaneous promotion and product quality have a positive and significant effect on the purchase decision of Aerostreet products in North Kedoya. This study has limited research on the place and variables used in the study.